3-A-D-2-17. Correlation between cerebrospinal fluid biomarkers of Alzheimer's disease and EEG activities assessed by eLORETA (exact Low Resolution Electromagnetic Tomography). Issue 6 (June 2015) - Hata, Masahiro; Tanaka, Toshihisa; Kazui, Hiroaki; Ishii, Ryouhei; Ikeda, Shunichiro; Aoki, Yasunori; Sato, Shunsuke; Suzuki, Yukiko; Kanemoto, Hideki; Yoshiyama, Kenji; Iwase, Masao; Takeda, Masatoshi
Abstract : To explore clues of early diagnosis of AD, we investigated the association between the cerebrospinal fluids (CSF) of Alzheimer's disease (AD) and the patients' EEG factors assessed by eLORETA. Fourteen probable AD patients with 40 s artifact-free EEG recordings were enrolled. The CSF samples were measured for total tau (T-tau), A β 40, and A β 42. EEG data were evaluated with eLORETA for current source density (CSD) and lagged phase synchronization (LPS) as functional connectivity. We analyzed the relationship between CSF measures and EEG parameters with regression analysis. The logarithmic values of CSD of the right temporal area in theta band (4–8 Hz) were negatively correlated with the concentration of A β 42 ( p < 0.05). In addition, the value of LPS between the left frontal eye field and the right auditory area in alpha 2 band (10–13 Hz) were also negatively correlated with the concentration of T-tau ( p < 0.05). These EEG characteristics could be related with the disturbances of cholinergic nerves and axonal projections, respectively. In this study, A β 42 of CSF was associated with CSD of EEG, likewise, T-tau was relevant to LPS of EEG. The prediction for CSF biomarkers based on EEG parameters could be helpful for early diagnosis of AD.